2022
DOI: 10.3389/fonc.2022.816427
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Methods and Social Factors Are Associated With Long-Term Survival in Follicular Thyroid Carcinoma: Construction and Validation of a Prognostic Model Based on Machine Learning Algorithms

Abstract: BackgroundThis study aimed to establish and verify an effective machine learning (ML) model to predict the prognosis of follicular thyroid cancer (FTC), and compare it with the eighth edition of the American Joint Committee on Cancer (AJCC) model.MethodsKaplan-Meier method and Cox regression model were used to analyze the risk factors of cancer-specific survival (CSS). Propensity-score matching (PSM) was used to adjust the confounding factors of different surgeries. Nine different ML algorithms,including eXtre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…It is noteworthy that our study concluded that patients with single, widowed and separated status had worse prognosis and marital status as one of the predictive factors affecting OS in LATC patients, while Li et al [ 26 ] also concluded that marital status in patients with TC was significantly associated with both CSS and OS. Previous studies have also concluded that good marital status has a positive effect on the prognosis of a variety of malignant tumors [ 27 ], and since TC, as an endocrine system disease, emotional changes and psychological well-being may be closely related to its prognosis, we believe that providing effective psychological counseling and social support to unmarried, widowed and separated patients may have a positive effect on the patients’ prognosis. Similarly, we only found that males had a worse prognosis than females in the predictive analyses of OS in the LATC patients, which is very similar to the findings of Li et al [ 28 ] However, Zhou et al [ 29 ] found that the prognosis of male patients with DTC did not differ from that of females after matching by propensity score.…”
Section: Discussionmentioning
confidence: 78%
“…It is noteworthy that our study concluded that patients with single, widowed and separated status had worse prognosis and marital status as one of the predictive factors affecting OS in LATC patients, while Li et al [ 26 ] also concluded that marital status in patients with TC was significantly associated with both CSS and OS. Previous studies have also concluded that good marital status has a positive effect on the prognosis of a variety of malignant tumors [ 27 ], and since TC, as an endocrine system disease, emotional changes and psychological well-being may be closely related to its prognosis, we believe that providing effective psychological counseling and social support to unmarried, widowed and separated patients may have a positive effect on the patients’ prognosis. Similarly, we only found that males had a worse prognosis than females in the predictive analyses of OS in the LATC patients, which is very similar to the findings of Li et al [ 28 ] However, Zhou et al [ 29 ] found that the prognosis of male patients with DTC did not differ from that of females after matching by propensity score.…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, we found that married middle-aged FTC patients reflected a longer survival time and better prognosis, consistent with previous studies related to thyroid cancer. Exploring the underlying reasons, in terms of psychosocial, economic or treatment adherence, we found that married patients may have a better prognosis due to better social support and mental health status [ 33 ]. Unmarried or divorced patients may face more psychological stress and less social support, which may affect their adherence to treatment and, thus, overall health [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the test set, the AUC, accuracy, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and F1 score were estimated. The best prediction model was selected by evaluating the largest AUC [ 47 , 48 ]. We applied the Shapley Additive Explanation (SHAP) to explain the best-performing predictive model.…”
Section: Methodsmentioning
confidence: 99%
“…The features were ordered by the mean absolute value of the SHAP values for each feature [ 44 ]. Combining ML with SHAP could provide an explicit explanation of the efficacy prediction [ 44 , 47 , 49 ]. The process is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%